De Novo Acute Heart Failure and Acutely Decompensated Chronic Heart Failure - Hummel, Astrid (Dtsch Arztebl Int, 2015)
BACKGROUND: Heart failure is one of the most common diseases of adults in Europe, with an overall prevalence of 1–2%. Among persons aged 60 and above, its prevalence is above 10% in men and 8% in women. Acute heart failure has a poor prognosis; it is associated with a high rate of rehospitalization and a 1-year mortality of 20–30%. METHODS: This review is based on pertinent literature, including guidelines, retrieved by a selective search in PubMed. RESULTS: There are different types of acute heart failure; the basic diagnostic assessment is performed at once and consists of ECG, echocardiography, and the measurement of N-terminal pro-brain natriuretic peptide (NTproBNP) and troponin levels. The most common causes of decompensation are arrhythmia, valvular dysfunction, and acute cardiac ischemia, each of which accounts for 30% of cases. The potential indication for immediate revascularization should be carefully considered in cases where acute heart failure is due to coronary heart disease. The basic treatment of acute heart failure is symptomatic, with the administration of oxygen, diuretics, and vasodilators. Ino-tropic agents, vasopressors, and temporary mechanical support for the circulatory system are only used to treat cardiogenic shock. CONCLUSION: The treatment of acute heart failure is markedly less evidence-based than that of chronic heart failure. Newer treatment approaches that are intended to improve outcomes still need to be tested in multicenter trials.